(untitled) (Global Journal of Human-Social Science, 2012)
Dhaka the capital of Bangladesh could be the best illustration of human activities and associated environmental change The capital Dhaka expanded rapidly between 1960 and 2005 built up areas increased approximately 15 924 ha while agricultural land decreased 7 614 ha vegetation decreased 2 336 ha wetland lowland decreased 6 385 ha and water bodies decreased about 864 ha The amount of urban land increased from 11 in 1960 to 34 in 2005 Historically the direction of urban expansion of Dhaka has greatly been constrained by the low elevation of lands surrounding rivers and risk of flooding also geomorphologic and hydrologically Dhaka city are greatly vulnerable to seasonal inundations The present paper discusses comparative analysis of urban growth and flood risk in newly buildup urban areas of Dhaka Bangladesh Both primary and secondary data have been used in the present research This study suggested comprehensive measures including structural and non structural measures that will be included a number of flood control and mitigation programs as well as alternative valuable resources for urban planners and decision makers to devise sustainable land use and environmental planning